Dengue and dengue haemorrhagic fever. - Rigau-Pérez, J; Clark, G; Gubler, D; Reiter, P; Sanders, E; Vorndam, A (1998)
The incidence and geographical distribution of dengue have greatly increased in recent years. Dengue is an acute mosquito-transmitted viral disease characterised by fever, headache, muscle and joint pains, rash, nausea, and vomiting. Some infections result in dengue haemorrhagic fever (DHF), a syndrome that in its most severe form can threaten the patient's life, primarily through increased vascular permeability and shock. The case fatality rate in patients with dengue shock syndrome can be as high as 44%. For decades, two distinct hypotheses to explain the mechanism of DHF have been debated-secondary infection or viral virulence. However, a combination of both now seems to be the plausible explanation. The geographical expansion of DHF presents the need for well-documented clinical, epidemiological, and virological descriptions of the syndrome in the Americas. Biological and social research are essential to develop effective mosquito control, medications to reduce capillary leakage, and a safe tetravalent vaccine.